2003
DOI: 10.1124/dmd.31.6.798
|View full text |Cite
|
Sign up to set email alerts
|

HEPATOBILIARY EXCRETION OF ACETAMINOPHEN GLUTATHIONE CONJUGATE AND ITS DERIVATIVES IN TRANSPORT-DEFICIENT (TR-) HYPERBILIRUBINEMIC RATS

Abstract: ABSTRACT:The involvement of the canalicular multidrug resistance protein 2 (Mrp2) in the hepatobiliary excretion of acetaminophen (APAP)-glutathione (GSH) conjugate and its derivatives was investigated using transport-deficient (TR Acetaminophen (APAP 1 ) is biotransformed through phase I and phase II reactions into negatively charged, hydrophilic metabolites that are eliminated in urine and bile. Cytochrome P450 converts APAP to the highly reactive electrophile N-acetyl-p-benzoquinoneimine (Dahlin et al., 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 25 publications
2
60
0
Order By: Relevance
“…Its endogenous substrates include tetrahydroxylated bile acids (Megaraj et al, 2010), divalent bile acids dmd.aspetjournals.org (Kuipers et al, 1988), glutathione (Oude Elferink et al, 1990), bilirubin glucuronosides (Paulusma et al, 1997), eicosanoids (prostaglandin E2, leukotriene C 4 ) , and conjugated steroids [estrone 3-sulfate (Kopplow et al, 2005), estradiol-17b-glucuronate ]. Exogenous ABCC2 substrates are mostly conjugated, either with glucuronic acid [e.g., phytoestrogens (Krumpochova et al, 2012), acetaminophen (Xiong et al, 2000), indomethacin (Kouzuki et al, 2000), morphine (van de Wetering et al, 2007)], sulfuric acid [e.g., acetaminophen (Zamek-Gliszczynski et al, 2005), resveratrol (Kaldas et al, 2003)], or with glutathione [e.g., acetaminophen (Chen et al, 2003a), bromosulfophthalein (Jansen et al, 1987), dinitrophenyl (Elferink et al, 1989)]. However, ABCC2 also transports unconjugated anionic drugs, such as pravastatin (Yamazaki et al, 1997), ampicillin (Verkade et al, 1990), and methotrexate (Hooijberg et al, 1999).…”
Section: Abcc2mentioning
confidence: 99%
“…Its endogenous substrates include tetrahydroxylated bile acids (Megaraj et al, 2010), divalent bile acids dmd.aspetjournals.org (Kuipers et al, 1988), glutathione (Oude Elferink et al, 1990), bilirubin glucuronosides (Paulusma et al, 1997), eicosanoids (prostaglandin E2, leukotriene C 4 ) , and conjugated steroids [estrone 3-sulfate (Kopplow et al, 2005), estradiol-17b-glucuronate ]. Exogenous ABCC2 substrates are mostly conjugated, either with glucuronic acid [e.g., phytoestrogens (Krumpochova et al, 2012), acetaminophen (Xiong et al, 2000), indomethacin (Kouzuki et al, 2000), morphine (van de Wetering et al, 2007)], sulfuric acid [e.g., acetaminophen (Zamek-Gliszczynski et al, 2005), resveratrol (Kaldas et al, 2003)], or with glutathione [e.g., acetaminophen (Chen et al, 2003a), bromosulfophthalein (Jansen et al, 1987), dinitrophenyl (Elferink et al, 1989)]. However, ABCC2 also transports unconjugated anionic drugs, such as pravastatin (Yamazaki et al, 1997), ampicillin (Verkade et al, 1990), and methotrexate (Hooijberg et al, 1999).…”
Section: Abcc2mentioning
confidence: 99%
“…Mrp2 and Bcrp are localized to the canalicular (apical) membrane of hepatocytes from which they excrete their substrates into the bile canaliculi. Accordingly, in a healthy liver, biliary excretion of the SULF, GLUC, and GSH conjugates of APAP is predominantly mediated by Mrp2, whereas Bcrp appears also to contribute to excretion of APAP-SULF conjugates (Büchler et al, 1996;König, 1997, 2000;Borst et al, 2000;Chen et al, 2003;Zamek-Gliszczynski et al, 2005). Mrp3 and Mrp4 are expressed at the sinusoidal (basolateral) membrane of hepatocytes and cholangiocytes from which they expel their substrates into the blood (König et al, 1999;Donner and Keppler, 2001;Soroka et al, 2001).…”
mentioning
confidence: 99%
“…In rats, excretion of APAP-GLUC and APAP-GSH metabolites from the liver occurs predominantly via the biliary route, whereas the APAP-SULF metabolite predominantly undergoes sinusoidal efflux and subsequent elimination in the urine (Gregus et al, 1988). Importantly, all APAP metabolites require efflux transport to be excreted from the liver, and each can be detected in both bile and urine (Gregus et al, 1988;Xiong et al, 2002;Chen et al, 2003;Manautou et al, 2005;Zamek-Gliszczynski et al, 2006a).…”
mentioning
confidence: 99%
“…Taken together, the results indicated that bile acids may play important roles in energy expenditure through regulating the mobility/storage of free fatty acids. The up-regulation of the expression of ATP-binding cassette genes Mrp2 and Mrp3 (also named as Abcc2 and Abcc3) may also be an attempt by the hepatocytes to transport residual APAP metabolites into the bile and portal blood [33,34]. APAP-GSH, APAP-NAC and APAP-Glu conjugates are substrates of MRP2 and MRP3 [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of the expression of ATP-binding cassette genes Mrp2 and Mrp3 (also named as Abcc2 and Abcc3) may also be an attempt by the hepatocytes to transport residual APAP metabolites into the bile and portal blood [33,34]. APAP-GSH, APAP-NAC and APAP-Glu conjugates are substrates of MRP2 and MRP3 [33,34]. These results are consistent with a xenobiotic detoxification metabolism wherein the expressions of Mrp and Mdr transporters are increased to facilitate the detoxification process [35][36][37].…”
Section: Discussionmentioning
confidence: 99%